1999
DOI: 10.1016/s0002-9270(99)00055-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system tone measured by baroreflex sensitivity is depressed in patients with end-stage liver disease

Abstract: Vagal tone, as assessed by BRS, is markedly depressed in cirrhotic patients awaiting liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, several potential mechanisms are known. Autonomic dysfunction, including cardiovascular instability, has been demonstrated to be associated with advanced liver disease in a number of settings, including in patients with PBC, and this undoubtedly will be found to contribute to the symptoms described in at least some of the patients 13–15, 35–39. It is most unlikely, however, that such features of advanced disease are responsible for a symptom complex present in almost three quarters of patients given the predominance of early‐stage disease and the very low prevalence of advanced liver disease and/or portal hypertension in the study population.…”
Section: Discussionmentioning
confidence: 94%
“…However, several potential mechanisms are known. Autonomic dysfunction, including cardiovascular instability, has been demonstrated to be associated with advanced liver disease in a number of settings, including in patients with PBC, and this undoubtedly will be found to contribute to the symptoms described in at least some of the patients 13–15, 35–39. It is most unlikely, however, that such features of advanced disease are responsible for a symptom complex present in almost three quarters of patients given the predominance of early‐stage disease and the very low prevalence of advanced liver disease and/or portal hypertension in the study population.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported the presence of an autonomic neuropathy in cirrhosis, and most authors agree that the presence of autonomic dysfunction is related with the severity of liver disease, irrespective of its aetiology (15, 16, 18). A decrease in BRS in cirrhotic patients has been described both in experimental (13, 21, 22) and clinical studies (6, 23–26). In most human studies, the severity of cirrhosis was established according to clinical parameters and Child–Pugh score.…”
Section: Discussionmentioning
confidence: 96%
“…Brain cholinergic dysregulation has also been reported in patients with cirrhosis and in models of liver failure (183). Interestingly, alterations in brain cholinergic signaling parallel with lower vagal tone in patients with cirrhosis (184, 185). …”
Section: The Role Of the Central Nervous Systemmentioning
confidence: 99%